Challenges of Older Patients' Knowledge About Warfarin Therapy - Sayeed Nasser BPharm (Hon); Judy Mullan PhD, FSHP, BPharm, BA; Beata Bajorek BPharm,DipHospPharm, PhD, GradCertEdStud (HighEd) (SAGE Publishing, 2012)
Objective : To review the challenges of warfarin education for older patients (aged 65 years or older) in terms of knowledge, access to warfarin education, and education resources. Methods : A quasi-systematic review of the literature was performed via electronic database searches (eg, Medline, Embase, Cumulative Index to Nursing and Allied Health Literature, International Pharmaceutical Abstracts, Meditext, and Google Scholar) from 1990 to May 2011. Results : The 62 articles reviewed found that improved patient knowledge results in better anticoagulation control. The review also found that between 50% and 80% of older patients have inadequate knowledge about the basic aspects of warfarin therapy (eg, action, benefits and risks, interactions with other drugs or foods, international normalized ratio management). Demographic factors, such as advancing age, lower family income, and limited health literacy, were found to inversely affect patients' warfarin knowledge, and access to warfarin education and information resources were often suboptimal in different practice settings. Finally, a number of educational strategies and resources that could be readily incorporated to improve the effectiveness of current warfarin education programs were extracted from the review. Conclusion : This comprehensive review highlights that education about warfarin in older patients is currently suboptimal and may in part contribute to poor therapeutic outcomes. This review article also acknowledges the need to identify, target, and develop educational strategies and resources to further improve older patients' knowledge about their warfarin therapy.